Antiproliferative Effects of Methanolic Extracts of Cryptocarya concinna Hance Roots on Oral Cancer Ca9-22 and CAL 27 Cell Lines Involving Apoptosis, ROS Induction, and Mitochondrial Depolarization. (14th October 2014) - Huang, Hurng-Wern; Chung, Yi-An; Chang, Hsun-Shuo; Tang, Jen-Yang; Chen, Ih-Sheng; Chang, Hsueh-Wei
Abstract : Cryptocarya -derived natural products were reported to have several biological effects such as the antiproliferation of some cancers. The possible antioral cancer effect of Cryptocarya -derived substances was little addressed as yet. In this study, we firstly used the methanolic extracts of C. concinna Hance roots (MECCrt) to evaluate its potential function in antioral cancer bioactivity. We found that MECCrt significantly reduced cell viability of two oral cancer Ca9-22 and CAL 27 cell lines in dose-responsive manners (P < 0.01 ). The percentages of sub-G1 phase and annexin V-positive of MECCrt-treated Ca9-22 and CAL 27 cell lines significantly accumulated (P < 0.01 ) in a dose-responsive manner as evidenced by flow cytometry. These apoptotic effects were associated with the findings that intracellular ROS generation was induced in MECCrt-treated Ca9-22 and CAL 27 cell lines in dose-responsive and time-dependent manners (P < 0.01 ). In a dose-responsive manner, MECCrt also significantly reduced the mitochondrial membrane potential in these two cell lines (P < 0.01 –0.05). In conclusion, we demonstrated that MECCrt may have antiproliferative potential against oral cancer cells involving apoptosis, ROS generation, and mitochondria membrane depolarization.